Blended learning engagement in public and private higher education institutions: a differential item functioning analysis of students' background - Adams, Donnie; Joo, Mabel Tan Hwee; Sumintono, Bambang; Pei, Oh Siew (Universiti Utara Malaysia Press, 2019)
Purpose – Digital technology has transformed teaching and learning in such a way that it seems imperative lecturers and institutions need to adapt and adopt a blended learning model of instruction across disciplines. However, there is a scarcity of studies to determine the degree of students’ engagement on blended or online university courses. The purpose of the study is to investigate students’ cognitive engagement, emotional engagement, and behavioural engagement in a blended learning model of instruction as well as specifically assesstheir engagement based on demographic factors such as age, gender, field of study, ethnicity, and type of institution in leading Malaysian public and private higher education institutions. Methodology – A non-experimental quantitative research design was employed in this study. 462 undergraduate and postgraduate students were sampled using the Blended Learning Readiness Engagement Questionnaire©. Subsequently, WINSTEPS Rasch model measurement software was used to determine the reliability and validity of the research instrument. Descriptive statistics and differential item functioning (DIF) were conducted to assess students’ engagement in a blended learning model of instruction with the latter analysing specifically on student’s demographic factors such as age,gender, field of study, ethnicity, and type of institution. Findings – Findings show high levels of engagement in blended learning activities among students in both public and private higher education institutions based on their cognitive, emotional, and behavioural engagement processes. Findings also indicates differences in students’ engagement based on demographic factors such as age, gender, field of study, ethnicity, and type of institution. Significance – The findings of this study will help lecturers reflect on their own teaching practices in this era of technology advancement where a blended learning model of instruction are given increased prioritisation and proliferation. Implications and recommendations for future research in blended learning practices are presented.